Adsorbate/adsorbent interactions in microporous zeolites: mechanistic insights from NMR relaxation and DFT calculations. (April 2023) - D'Agostino, C.; Bräuer, P.; Zheng, J.; Robinson, N.; York, A.P.E.; Song, L.; Fan, X.
Abstract: Nuclear magnetic resonance (NMR) relaxation is an effective and non-invasive technique for probing guest-host interactions in porous materials. In particular, the ratio of longitudinal-to-transverse nuclear spin relaxation time constants T 1 / T 2 has been demonstrated as a robust indicator of adsorbate/adsorbent interactions in mesoporous media. However, the use of NMR relaxation times in microporous materials to probe interactions and dynamics remains relatively unexplored. Herein, we investigate and describe the effect of the aluminium content in microporous HZSM-5 zeolites on the NMR relaxation times of a range of common liquid probe molecules. In particular, we discuss the NMR relaxation time behavior of liquids with hydrophilic (water, methanol) and hydrophobic (toluene, methyl cyclohexane) properties adsorbed over HZSM-5 samples with varying silica-to-alumina ratios (SAR = SiO2 /Al2 O3 ). Our results demonstrate that highly polar molecules show high sensitivity to aluminium content (i.e., surface acidity), with T 1 / T 2 ratios increasing significantly for higher acidity zeolites. Conversely, for molecules with low polarity, the T 1 / T 2 ratio as a function of SAR remains approximately constant, and in the zeolites with low SAR is much lower compared to that of water and methanol. Density functional theory (DFT) calculations are employed to contrast the surface interaction mechanisms of water and toluene within model zeolite structures of varying SAR, and provide molecular level insights into the observed trends in NMR relaxation behavior. Graphical abstract: Image 1 Highlights: NMR relaxation is used to study adsorbate/adsorbent interactions in zeolites. Interactions of highly polar molecules are very sensitive to Al content. Interactions of low-polarity molecules do not show strong dependence on Al content. DFT calculations are used to elucidate mechanistic insights.